Long-Term Capital Movements - Lane, Philip (IMF Working Papers; Working Paper ;, 2001)
International financial integration allows countries to become net creditors or net debtors with respect to the rest of the world. In this paper, we show that a small set of fundamentals-shifts in relative output levels, the stock of public debt and demographic factors-can do much to explain the evolution of net foreign asset positions. In addition, we highlight the role that "external wealth" plays in determining the behaviour of the trade balance, and we provide some evidence that a portfolio balance effect exists: real interest rate differentials are inversely related to net foreign asset positions.